Ashley Hope Pérez. Deformative Fictions. Cruelty and Narrative Ethics in Twentieth-Century Latin American Literature. The Ohio State University Press, 2024. - Daniela Dorfman (Studies in 20th & 21st Century Literature, 2026)
Review of Ashley Hope Pérez. Deformative Fictions. Cruelty and Narrative Ethics in Twentieth-Century Latin American Literature. The Ohio State University Press, 2024. xiv+241 pp.
Keywords: literature; Spanish